Nef increases the synthesis of and transports cholesterol to lipid rafts and HIV-1 progeny virions - Zheng, Yong-Hui (National Academy of Sciences, 2003)
HIV buds from lipid rafts and requires cholesterol for its egress from and entry into cells. Viral accessory protein Nef plays a major role in this process. In this study, it not only increased the biosynthesis of lipid rafts and viral particles with newly synthesized cholesterol, but also enriched them. Furthermore, via the consensus cholesterol recognition motif at its C terminus, Nef bound cholesterol. When this sequence was mutated, Nef became unable to transport newly synthesized cholesterol into lipid rafts and viral particles. Interestingly, although its levels in lipid rafts were not affected, this mutant Nef protein was poorly incorporated into viral particles, and viral infectivity decreased dramatically. Thus, Nef also transports newly synthesized cholesterol to the site of viral budding. As such, it provides essential building blocks for the formation of viruses that replicate optimally in the host.